PERAN PESANTREN DALAM PENDIDIKAN ANAK DI ERA MODERN: Integrasi Nilai Keislaman, Karakter, dan Tantangan Global - Lila Hikmawati; Babun Suharto; Imam Syafi'i (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
Pesantren are Islamic educational institutions that have played a historical and strategic role in shaping children’s character and instilling Islamic values. In the modern era, children’s education faces multidimensional challenges arising from globalization, the rapid development of digital technology, and shifts in social and cultural values. This article aims to systematically examine the role of pesantren in children’s education in the modern era, with a particular focus on the integration of Islamic values, character formation, institutional challenges, and strategies for strengthening the role of pesantren. This study employs a qualitative approach using a Systematic Literature Review (SLR) method, drawing on relevant scholarly sources, including journal articles, academic books, and policy documents. The findings indicate that pesantren function as value-based educational institutions that integrate religious education, formal education, and daily life guidance through a boarding school system. This educational model enables the consistent internalization of Islamic values and character development in children. Nevertheless, pesantren face significant challenges, including the rapid advancement of digital technology, changes in students’ characteristics, and increasing demands for educational quality improvement. Therefore, strengthening integrative curricula, enhancing educators’ competencies, and the wise utilization of technology are key strategies to maintain the relevance of pesantren in children’s education in the modern era.